Assessment of Coagulation Tests in Hospitalized COVID19 Patients; Challenging Coagulopathies. (28th October 2021) - Barouqa, Mohammad; Szymanski, James; Rahman, Shafia; Lugo, Jesus Gonzalez; Billett, Henny; Sekhri, Radhika; Reyes, Morayma
Abstract: COVID-19 has caused a worldwide illness and New York has become the epicenter of COVID-19 in the United States. During the last year, The Bronx, one of the five boroughs of New York City, had the highest prevalence per capita in New York making it the epicenter of the pandemic. During the first wave of the pandemic, almost every labratory received tremendous amount of tests, and here we examined demographic and laboratory data, as well as trajectories of laboratory results, in order to determine the relation between these laboratory parameters, in particular tests of coagulation, to illness severity and mortality. Methods : This is a retrospective study of all positive COVID cases who were admitted between 2/22/2020-4/20/2020 at Montefiore Health System (MHS), a large tertiary care center in the Bronx. Together the ambulatory and hospital networks care for 2.8 million visits a year. All adults with positive COVID tests performed by MHS and who were admitted between 2/22/2020-4/20/2020 are considered. All hospitalized COVID positive cases were queried from the electronic medical record system. Physiological, demographic (age, sex, socioeconomic status and self-reported race and/or ethnicity) and laboratory data was captured. A subset of cases were chart-reviewed for accuracy and additional information. Statistical analysis was performed using R studio. Results : Discharge from hospital and mortality were the primary measured outcomes. 7096 patients tested positive for COVID, of which 2897 had an associated inpatient admission and 845 patients were seen in the ER and then discharged. A total of 767 COVID positive patients died during hospitalization. A multivariable logistic regression analysis shows increased odds ratio for mortality by age, gender(males > females), BMI, neutrophil to lymphocyte ratio, Charlson Score, and D-Dimer. The receiver operating characteristic curve (ROC) of D-Dimer combined with age showed an area under the curve (AUC) of 0.77. The optimal cut-point, calculated using Youden's index, for the initial D-Dimer to predict mortality was found to be 2.43ug/ml. D-Dimer trajectories between survivors and non-survivors showed a clear separation for non-survivors since admission. Conclusions: In this study we comprehensively studied demographic, physiological and laboratory parameters of COVID19+ minority patients in the Bronx, NYC, USA. This study confirms laboratory and clinical observations made by Wuhan studies of COVID19 infected patients. In particular the association of initial D-Dimer and its trajectory during hospitalization with mortality.